Implementation of the Job Creation Law on Legal Protection for Indonesian Migrant Workers - Reza Bayuna; Thamrin S; Surizki Febrianto; Lidia Febrianti (International Conference On Law And Social Sciences, 2024)
The risks of becoming a migrant worker are certainly not small, so they often need protection from the government. Many Indonesian migrant workers often receive poor treatment. The presence of the Job Creation Law does not reflect justice for workers and is considered pro-employer. Policies regarding workers' wages, permits and land control will result in the loss of the right to a living wage, the right to housing and a decent life. This research is normative legal research. Normative Legal Research is a process of finding legal rules, legal principles and legal doctrines to answer the legal issues faced.